Pemimpin Berjiwa Kastratur Ri’ayah wal Istima’ dalam Lingkup Grassroots - Sari, Prima Rosita; Alwatasi, Umar; Masduki, Yusron (Lembaga Yasin AlSys, 2023)
Grassroots or commonly referred to as grassroots appear as an alternative to solving problems that exist in society, especially in rural communities. This has something to do with the soul of a leader, where to be a leader must be able to play an important role, namely being able to provide innovation, motivation, form a shared vision and mission, and also form broader network relations. Leadership is the main thing in human life. By looking at various literature and literature reviews trying to examine Islamic leadership based on the Qur'an and Hadith in the scope of grassroots. As a leader and also leadership has such a close relationship that these two elements cannot be separated. This style of leader is a reflection of leader behavior, in which these two things are the main key in the successful management of an organizational system. Being a leader must have a spirit of ri'ayah wal istima' and also implement the four obligatory characteristics of Allah SWT, namely sidiq, amanah, tabligh, and fathonah. As well as making better leadership will also produce good output from something he leads. The credibility of being a leader also shows an expertise or expert power, accompanied by the positive habits of a leader. This becomes the main point in the soul of a leader to form a vision and mission, in order to run the wheels of the organization he is leading to achieve the goals that have been set.